Autopilot Drone - Þórarinn Árni Pálsson 1992- (2017)
This products initial development is a part of a school class at Reykjavík University called RT-LOK1012 which amounts to 24 ECTS. This report list the progress after one semesters work of development. This paper lists the process of making a steering mechanism for an autonomous boat which is to be able to sail by predefined coordinates wirelessly. The scope of this project was to research, test and assemble a prototype of an autopilot which could be used to resemble the final product that will be used in an autonomous boat.